What is Your Perception of Beauty? Culture Communication From Generation to Generation - Tina Kartika; Karomani Karomani (UIN Salatiga, 2021)
The research objective is to describe the communication culture about what is meant by beauty. Research is useful for knowing the perceptions of the Indonesian people. Impact on daily behavior, cosmetics and clothes used. Furthermore, it has an impact on the economy of the community, especially for companies and the media to advertise a product. Behavior is motivated by multi-ethnic, multi-religious and daily social communities, continuously from generation to generation. Using qualitative methods, and respondents numbered 100 people. Research Result : 1. Beauty does not mean only physical attractiveness, and still less only the physical appearance of women. 2. The concept of beauty in good behaviour when relating to others, 3. The concept of beauty in an individual’s pious duty to God. 4. The concept of beauty in a society includes values and mores that are inherited, or at least widely accepted, crystallize on the appearance and behavior of women.